Updates on the commercialization of medicines containing substances isolated from cannabis sativa in Brazil (Research, Society and Development, 2023)
In 1970, Cannabis sativa was described as an illegal substance, but is currently legalized in regions such as the Netherlands and the United States, being effective to assist in the treatment of diferente diseases. In Brazil, the criteria for importing products derived from Cannabis sativa by individuals, previously used only in therapeutic use in difficult-to-control epilepsies or neurological disorders, were defined. Therefore, the objective of this work was to carry out an update on medicines containing Cannabis sativa and its derivatives as an active ingredient that are authorized to be marketed in Brazil, based on the regulations controlled by ANVISA. Given these facts, the theoretical essay, based on a literature review, analyzes the impact of the use of Cannabis sativa drugs and its derivatives, which are authorized to be marketed in Brazil, based on changes in Brazilian legislation controlled by the National Surveillance Agency Sanitary (ANVISA). Updates on the use of medicinal products based on Cannabis sativa and its derivatives demonstrate several favorable therapeutic uses, highlighting cannabidiol, which was the first substance released for local production in Brazil, in 2020, based on the Resolution of the Collegiate Board of Directors (RDC) of 2019. Currently, 18 Cannabis-based products are approved by Anvisa, as provided for in RDC 327/2019.